2011
DOI: 10.1186/1748-5908-6-64
|View full text |Cite
|
Sign up to set email alerts
|

Collaborations for Leadership in Applied Health Research and Care: lessons from the theory of communities of practice

Abstract: BackgroundThe paper combines the analytical and instrumental perspectives on communities of practice (CoPs) to reflect on potential challenges that may arise in the process of interprofessional and inter-organisational joint working within the Collaborations for Leaderships in Applied Health Research and Care (CLAHRCs)--partnerships between the universities and National Health Service (NHS) Trusts aimed at conducting applied health research and translating its findings into day-to-day clinical practice.Discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 58 publications
2
106
0
2
Order By: Relevance
“…[39][40][41][42][43][44][45][46] The reports to date highlight similarities and differences between structural and content features of the CLAHRCs and point to early successes and challenges. For example, successes include strengthened networks and relationships; 39,44,47 new organisational roles that 'make sense to professionals'; collective action to improve practices; 48 and creating a culture of reflection and learning.…”
Section: Collaborations For Leadership In Applied Health Research Andmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43][44][45][46] The reports to date highlight similarities and differences between structural and content features of the CLAHRCs and point to early successes and challenges. For example, successes include strengthened networks and relationships; 39,44,47 new organisational roles that 'make sense to professionals'; collective action to improve practices; 48 and creating a culture of reflection and learning.…”
Section: Collaborations For Leadership In Applied Health Research Andmentioning
confidence: 99%
“…Baumbusch et al 91 explain how project meetings were used to feed back emerging findings for practitioners to action, and for practitioners to provide context that would assist interpretation of the findings. Kislov et al 40 describe such events and artefacts as 'boundary objects'. Others also write of the importance of colocating the partners, which facilitates not only formal face-to-face meetings but also informal discussion 'at the water cooler'.…”
Section: Process Factorsmentioning
confidence: 99%
“…It has been suggested that theory is not sufficiently utilised in the context of implementation research (Kislov et al, 2011). With regard to communities of practice, the literature surfaces two distinct theoretical propositions about the instrumental use of communities of practice and how their cultivation might improve collaborative responses in such a way as to impact on service user outcomes.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…In the healthcare sector, they have mostly been developed as unprofessional entities. Here, there is evidence that can play a role in the generation of social, human, organisational, professional and patient capital thus being useful for enhancing care, providing learning opportunities, analysing practice, problem solving, sharing knowledge and generating ideas (Kislov et al 2011). Much less is known about the development of interdisciplinary communities of practice (Kilbride et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been increasingly used as a theoretical approach to analyze and compare large-scale health care collaborations 1,5,8 . Additionally, a number of recent research findings have suggested that features of cop might be beneficial in addressing the challenges of multi-professional, multi-organizational collaborations [9][10][11] .The present paper attempts to close the gap between cop conceptualization and its application in health care settings by describing a working model that was used in the implementation of regional cops in cancer surgery. In addition, we explore the nature of peer networks within health care organizations and the opportunity for integrating existing networks from independent hospitals within a region into a manageable community.…”
mentioning
confidence: 99%